Penerapan Pasal 303 KUHP Berbasis Digital Judi Online Jo UU No. 19 Tahun 2016 Perubahan Atas UU No. 11 Tahun 2008 Tentang ITE - Astuti, Cindy Dwi; Heliany, Ina (FOCUS, 2025)
At present, online digital gambling is very common in Indonesia, this gambling not only involves adults but also teenagers, especially the younger generation. That the legal rules have been regulated in the Criminal Code related to online gambling, but in fact in the field law enforcement officers have difficulty and even seem to allow online gambling crimes. How is the Implementation of Article 303 of the Criminal Code related to the crime of digital-based online gambling and How is the regulation of Online Gambling Crimes reviewed from the Perspective of the Criminal Code and Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions. This study uses the Normative Juridical research method. The method applied in this study is a qualitative descriptive method. The results of the study show that the application of Article 303 of the Criminal Code to online digital-based gambling crimes is no longer relevant because Article 303 of the Criminal Code does not regulate the elements of information technology. In Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions, there are still weaknesses in its implementation. The government together with related institutions need to design more specific regulations to handle online digital-based gambling, which includes stricter law enforcement against all parties, including online gambling perpetrators. The need for legal reforms against online digital-based criminal crimes to special crimes so as not to damage the nation's generation and the nation's economy.